(untitled) (Baghdad Science Journal, 2012)
In this study , Iraqi Bentonite clay was used as a filler for polyvinyl chloride polymer. Bentonite clay was prepared as a powder for some certain particle size ,followed by calcinations process at (300,700,900) OC ,then milled and sieved. The selected sizes were D 75 µm and D 150. After that polyvinyl Al-Cohool solution prepared and used as a coated layer covered the Bentonite powder before applied as a filler ,followed by drying , milling and sieving for limited recommend sizes. polyvinyl chloride solutions were prepared and adding of modified Bentonite power at certain quantities were followed .Sheet of these variables on the mechanical and thermal properties of the prepared reinforced particular polyvinyl chloride composite Experimentally, it was found that the composite prepared by adding modified Iraqi Bentonite powder , that calcined at 700 oC as a filler have an advantage in heating insulator properties by 30 from that found for PVC as it is ,and the value of stress strength exceed by three times as that for original value.